Intensive English language program for overseas students at Malaysian private tertiary education institutions - Nurtjahja, Oktavia R.; Sabani, Noraisikin (Faculty of Communication and Modern Languages, Universiti Utara Malaysia, 2007)
As Malaysia is positioning itself to be a regional center of educational excellence, efforts are taken to recruit international students from other countries in the region to pursue international tertiary education, with English as the language of instruction. It is an acceptable fact that most countries within the region place English as a foreign language, thus, the majority of students coming from these countries do not possess the command of English language required to study at a tertiary level. Therefore, as an international education provider, Malaysia has to cater for this need. This paper aims to highlight the competitive advantages and limitations that Malaysia has in terms of providing the English language program that overseas students need. It also explores possible strategies to overcome the limitations. The discussion is focused on Malaysian private tertiary education institutions. It mainly stemmed from a critical analysis of Malaysian education system as well as the socio and cultural aspects of Malaysia. It also incorporates data from informal discussions with English teachers and international students.